Subsidies as a regulatory object: From trade subsidies to outward FDI subsidies - Keer Huang (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
As the scope of the rules on subsidies and countervailing measures has expanded from trade to investment, the area of global subsidy regulation is now experiencing new developments as well as challenges. This Perspective calls attention to the need to improve the regulation of OFDI subsidies.
Keywords: 330